Comparative Analysis on the Primary English Curricula of Japan and Indonesia - T Tuswadi (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2016)
Abstract Primary English education in Indonesia and Japan is developing rapidly nowadays. Children in both countries have started to learn English since they are at least in grade four or five. Although English is not a compulsory subject in primary schools, the interest of schools in the two countries toward English education for children is getting higher. This paper tried to reveal the similarities and differences of primary English curiculum contents in Indonesia and in Japan in order to understand better about the development of English education in primary schools in the two countries. Abstrak Pendidikan bahasa Inggris dasar di Indonesia dan Jepang berkembang pesat saat ini. Anak-anak di kedua negara tersebut sudah mulai belajar bahasa Inggris setidaknya sejak mereka kelas empat atau kelas lima. Meskipun bahasa Inggris bukan mata pelajaran wajib di sekolah dasar, minat sekolah-sekolah di kedua negara terhadap pendidikan bahasa Inggris untuk anak-anak semakin tinggi. Tulisan ini mencoba untuk mengungkapkan persamaan dan perbedaan isi kurikulum bahasa Inggris dasar di Indonesia dan di Jepang untuk memahami lebih baik tentang perkembangan pendidikan bahasa Inggris di tingkat sekolah dasar di kedua negara. How to Cite : Tuswadi. (2016). Comparative Analysis of the Primary English Curricula of Japan and Indonesia. TARBIYA: Journal Of Education In Muslim Society, 3(1), 96-106. doi:10.15408/tjems.v3i1.3224. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v3i1.3224